Influence of Wild Bee Diversity on Canola Crop Yields - Halinski, Rosana; dos Santos, Charles Fernando; Kaehler, Tatiana Guterres; Blochtein, Betina (Sociobiology, 2018)
The foraging range of bees determines the spatial scale over which each species can provide pollination services. In agricultural ecosystems, productivity is related not only to the taxonomic diversity of bees per se, but also to the location of their nesting sites, which reflects on their flying range. Within this context, the present study sought to assess how wild bee assemblages affect the yield of Brassica napus at three different distances (25 m, 175 m, 325 m) from forest remnants in Southern Brazil. Bees were sampled by means of pan traps and findings were analyzed using the Shannon diversity index and generalized linear models. We identified 11 species of native bees, both solitary and social, as well as the exotic species Apis mellifera, which was most abundant. Our findings show that canola crop yield were positively influenced by the diversity of bee species. This demonstrates that native bees, not only A. mellifera, can contribute significantly to the productivity of canola crops. In addition, we found that bee body size is significantly associated with flight distance traveled within the canola fields, and demonstrated a relationship with nesting sites. Thus, we hypothesize that canola yields are associated with the presence of wild bee species, both social and solitary, and that maintenance of these pollinators is directly dependent on practices adopted in rural areas, whether within plantation fields per se or in forest remnants used as nesting sites by wild bees.